Thermal diffusion and diffusion thermo effects on MHD thermosolutal Marangoni convection boundary layer flow over a permeable surface - Rohana, Abdul Hamid; Wan Mohd Khairy Adli, Wan Zaimi; Norihan, Md Arifin, Dr.; Nor Ashikin, Abu Bakar; Biliana, Bidin (Hindawi Publishing Corporation, 2013)
Link to publisher's homepage at http://www.hindawi.com/